Sustainable tourism education at a crossroads: Bibliometric insights and a strategic research framework - Yoopetch, Chanin; Kongarchapatara, Boonying (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the evolution, intellectual architecture, and future frontiers of Sustainable Tourism Education (STE) in alignment with global sustainability agendas. A bibliometric analysis was conducted using the PRISMA framework to systematically select 1,842 peer-reviewed publications from the Scopus database spanning 1989 to early 2025. VOSviewer was employed for data visualization and network analyses, including citation, co-citation, and keyword co-occurrence. The findings reveal a significant growth trajectory in STE research, particularly since 2017, with dominant contributions from Australia, the United States, and the United Kingdom, alongside increasing research productivity from emerging economies such as Malaysia, Indonesia, and India. Four primary thematic clusters are identified: environmental education, sustainable development planning, higher education for economic development, and geotourism. However, the results indicate a strong emphasis on environmental and economic dimensions, while social and cultural aspects remain underexplored. Overall, STE has evolved into a multidisciplinary and globally expanding field, though notable thematic imbalances persist. The study offers practical implications by proposing a strategic research agenda that emphasizes interdisciplinary collaboration and greater integration of social and cultural perspectives, thereby guiding educators, researchers, and policymakers to enhance the long-term effectiveness and global impact of sustainable tourism education.